2017
DOI: 10.1002/cphc.201700320
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of an Ethylene Carbonate/Diethyl Carbonate Mixture by Using Ionizing Radiation

Abstract: The reactivity of ethylene carbonate (EC) and of a EC/diethyl carbonate (DEC) mixture was studied under ionizing radiation to mimic the aging phenomena that occur in lithium‐ion batteries. Picosecond‐pulse radiolysis experiments showed that the attachment of the electron to the EC molecule is ultrafast (k(e−EC+EC)=1.3×109 L mol−1 s−1 at 46 °C). This reaction rate is accelerated by a factor of 5.7 compared with the electron attachment to propylene carbonate, which implies that the presence of the methyl group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…In the viscoelastic model, three parameters (fluid density, fluid viscosity, and layer density) were specified and kept fixed throughout. The density and viscosity of EC/DEC (1:1 v / v ) have been reported in the literature; the values are 1160 kg m −3 and 0.00164 kg m −1 s −1 , respectively . The density of the polymer–solvent interacting layer (L1) was approximated to have the same density as the EC/DEC solvent, 1160 kg m −3 .…”
Section: Methodsmentioning
confidence: 99%
“…In the viscoelastic model, three parameters (fluid density, fluid viscosity, and layer density) were specified and kept fixed throughout. The density and viscosity of EC/DEC (1:1 v / v ) have been reported in the literature; the values are 1160 kg m −3 and 0.00164 kg m −1 s −1 , respectively . The density of the polymer–solvent interacting layer (L1) was approximated to have the same density as the EC/DEC solvent, 1160 kg m −3 .…”
Section: Methodsmentioning
confidence: 99%
“…FID [234] FTIR [198] MS [198,235] TCD [234,[236][237][238][239][240] VUV [217] n/a [241,242] Model Aging of LIB Components (Thermal; Radiolysis, etc.) FTIR [243,244] MS [151,207,208,211,[243][244][245][246][247][248][249][250] TCD [207,208,249,250] n/a [251][252][253] The analyses of permanent gases emerging during the formation procedure was investigated by a variety of different research groups. Yoshida et al [57] focused their work on open prismatic cells and their findings are already discussed in 3.3, while Ota et al [228] used an assembly-type cell (stainless steel).…”
Section: Origin Of the Gases Detector Referencesmentioning
confidence: 99%
“…The authors concluded that the high dose rate radiolysis may mimic, with a fair approximation and within much shorter times, the degradation processes involved in electrochemical experiments. Further investigations focusing on radiolysis experiments as model aging techniques of LIB electrolytes and their components were performed by Wang et al, who investigated the differences between single carbonates and their binary mixtures [249]. Varenne et al used radiolysis in presence of active materials to investigate the forming agglomerates [250].…”
Section: Origin Of the Gases Detector Referencesmentioning
confidence: 99%
“…[14][15][16] Moreover, radiolysis enables performing time-resolved experiments, and with a high time resolution (picosecond timescale), the kinetic data on the first processes at stake in the system of interest can be obtained. [15,[17][18] Radiolysis thus constitutes an accelerated chemical approach to fundamentally study the behavior of different electrolytes or the different solvents that constitute electrolytes. It can provide information on the behavior of FEC whose reaction mechanisms in the batteries are debated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A few hours are necessary in the case of radiolysis against several months or even years in the conventional method [14–16] . Moreover, radiolysis enables performing time‐resolved experiments, and with a high time resolution (picosecond timescale), the kinetic data on the first processes at stake in the system of interest can be obtained [15,17,18] . Radiolysis thus constitutes an accelerated chemical approach to fundamentally study the behavior of different electrolytes or the different solvents that constitute electrolytes.…”
Section: Introductionmentioning
confidence: 99%